Legal Existence of Brokers in Land Sale and Purchase Binding Agreement - Nurlaila Kadarwati Papuluwa; Husen Alting; Suwarti Suwarti (Syntax Corporation Indonesia, 2022)
This study aims to analyze the legal position of the broker (broker) as an intermediary trader in the binding agreement for the sale and purchase of land in Indonesia, as well as the legal implications of the actions of the land broker in the binding sale and purchase agreement (PPJB) which resulted in the occurrence of defect of will(wilsgebreken/ defect of consent). This type of research uses the normative type, normative legal research is a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. The results of this study indicate that legal position of a broker (broker) as an intermediary trader in a binding agreement for the sale and purchase of land in Indonesia in the KUHD arrangement is classified based on an official broker and an unofficial broker. Related official brokers have been regulated in the provision of Article 62 of the KUHD that he must obtain an official appointment fromrequired state officials. Meanwhile, unofficial brokers through the provisions of Article 63 of the KUHD do not grant a monopoly position to brokers, in fact there is an article that allows the existence of unofficial brokers, namely without an appointment from the Minister of Justice and without an oath, namely Article 63 of the KUHD bsd 1792 of the KUHPER. In this case, this unofficial broker is seen as a normal power holder